Characteristics of Chitooligosaccharides Hydrolysate from Crab Shell (Portunus Pelagicus) Waste by Chitosanase Hydrolysis - Mohammad Rafi Prasetyo; Ulya Sarofa; Rosida R (Food Science and Technology Journal (Foodscitech), 2021)
Enzymatic hydrolysis of chitooligosaccharides can be carried out using the chitosanase enzyme. Chitosanase enzyme is a glycosyl hydrolase enzyme that catalyzes the hydrolysis of β- 1,4 glycosidic bonds of chitosan to produce low molecular weight chitooligosaccharides. The crab shell (Portunus pelagicus) has the potential to be used as chitooligosaccharides because the crab shell contains 20-30% chitin. This study aimed to determine the effect of chitosanase enzyme concentration and duration of hydrolysis on the characteristics of chitooligosaccharides (COS) from crab shells. This research was conducted using a factorial completely randomized design (CRD) method with two factors and two replications. The factor I was enzyme concentration (0.5%, 1%, and 1.5%), factor II was hydrolysis time (3 hours, 4 hours and 5 hours). The data were obtained using ANOVA if there was a significant difference, followed by Duncan's Test (DMRT). The best results were obtained in the A2B2 treatment, enzyme concentration (1.0%) and hydrolysis time (4 hours) with a chemical composition of 84.96% yield, 4.83 KDa molecular weight, 86.87% degree of deacetylation and FTIR test results indicated the availability of a functional groups, the OH group was obtained at a wavelength of 3624.25 cm-1 and the NH group is at a wavelength of 3404.36 cm-1.